Academic and Resident Radiation Oncologists' Attitudes and Intentions Regarding Radiation Therapy near the End of Life. (February 2016) - Lloyd, Shane; Dosoretz, Arie P.; Yu, James B.; Evans, Suzanne B.; Decker, Roy H.
Abstract : Objectives: There has been increasing scrutiny about cancer treatment for patients very near the end of life (EoL), yet a substantial number receive palliative radiation therapy (RT) in this setting. Our aim was to document the attitudes and intentions of thought leaders and trainees in giving RT near the EoL. Methods: We distributed an anonymous survey to 473 radiation oncologists and residents. The survey examined the clinical and psychosocial factors considered as well as intentions and expectations in the delivery of RT near the EoL. Factors surrounding unfinished treatment courses, and the formative factors that shape opinions about RT at the EoL were also explored. Results: We received 139 responses (29%). Eighty-nine percent of respondents worked at academic institutions. The factors that respondents most often consider very or extremely important to offer RT near the EoL were the preference of the patient to be treated (94%), the ability to tolerate treatment (88%), and palliative intent (70%). After instances when their patients were unable to complete treatment near the EoL, 42% of respondents said they would prescribe a shorter treatment the next time they see a similar patient. Personal experience (71%) was most often listed as very or extremely important in shaping their opinions about RT near the EoL. Conclusions: Survey respondents, 89% of whom were academic radiation oncologists, have a positive view of palliative RT near the EoL. They favor shorter fractionation for patients near the EoL. Personal experience is most important in shaping practices and attitudes. Abstract : Supplemental Digital Content is available in the text.